Kidney stones and moderate proteinuria as the rare manifestations of Gitelman syndrome - Chen, Qi (BMC Nephrol, 2021)
BACKGROUND: Gitelman syndrome (GS) is an autosomal recessive inherited salt-losing tubulopathy (SLT). Here, we describe, for the first time, a case of GS without Gitelman-like features and with concomitant kidney stones, cysts and diabetic nephropathy (DN). CASE PRESENTATION: We described a male patient had a 19-year history of recurrent fatigue. From childhood, he had polydipsia and polyuria, paroxysmal tetany and palpitation. Serum biochemistry revealed chronic hypokalemia, metabolic alkalosis, normomagnesemia, mildly elevated Cr. Concomitant 24 h urine collection showed inappropriate renal potassium wasting, borderline hypercalciuria, moderate proteinuria consisting of major glomerular. Ultrasound of urinary tract showed bilateral and multiple kidney stones and cysts. Whole exome sequencing (WES) identified compound heterozygous mutations of SLC12A3. The unusual association of SLTs and glomerular proteinuria prompted us to perform a renal biopsy. Renal pathology showed renal involvement consistent with GS and early stage of diabetic nephropathy (DN). After treatment with KCl, magnesium oxide, perindopril and acarbose, the patient had been cured. The fatigue didn’t relapse. CONCLUSION: GS had high variability of phenotype, GS may have no Gitelman-like features, kidney stones are not the exclusion criteria of GS. Renal biopsy should be warranted for GS patients with moderate to massive glomerular proteinuria.